A new, disjunct, diplopod genus from Espirito Santo, Brasil (Polydesmida: Chelodesmidae) - Hoffman, Richard L. (Papéis Avulsos de Zoologia, 2009)
The new generic and specific names Cryptosolenomeris macrogon are proposed for a large chelodesmoid milliped collected at Linhares, Espírito Santo, Brazil, and characterized particularly by the elongated gonotelopodites lacking torsion and apically recurved into a calyciform shield concealing the solenomere; the typical chelodesmoid prefemoral process appears to be either undeveloped or present in a disjunct position. There are no known close generic relatives in the known Brazilian fauna.